Analisis Resistensi Bakteri terhadap Antibiotik pada Pasien dengan Berbagai Golongan Darah - Amelia Putri Az Zahra; Pramesti Listanto; Latifa Alya Khairunnisa; Juwita Ramadhani Octavianingrum; Liss Dyah Dewi Arini (Jurnal Mahasiswa Ilmu Kesehatan, 2025)
Acinetobacter baumannii is a major pathogenic bacterium causing nosocomial infections, known to exhibit high levels of resistance to various antibiotic classes, including β-lactams and aminoglycosides. This widespread resistance poses a significant challenge in hospital patient management, particularly in cases of severe and difficult-to-treat infections. This study aimed to analyze the resistance patterns of A. baumannii to four types of antibiotics in patients with various blood types at Dr. Soeradji Tirtonegoro General Hospital, Klaten. The research method used was a qualitative approach with a case study design. Data were obtained through in-depth interviews with healthcare workers, analysis of patient medical records, and limited observation of clinical practice. The focus of the study was directed at the relationship between patient blood type and the level of antibiotic resistance of A. baumannii. The results showed variations in resistance patterns based on blood type. Patients with blood type AB showed the highest level of resistance to all tested antibiotics, with a prevalence of multidrug resistance (MDR) reaching 85%. In contrast, patients with blood type O showed the lowest resistance and the highest proportion of non-MDR isolates compared to other groups. These findings indicate the role of host factors, namely blood type, in influencing the level of resistance of A. baumannii. The suspected mechanisms involved include differences in surface antigens that influence bacterial adhesion, biofilm formation, and the host immune response. The practical implication of this study is the need to consider blood type as a factor in empirical antibiotic therapy, especially in cases of nosocomial infections caused by A. baumannii.